2008
DOI: 10.1007/s00453-008-9227-6
|View full text |Cite
|
Sign up to set email alerts
|

Well Supported Approximate Equilibria in Bimatrix Games

Abstract: In view of the apparent intractability of constructing Nash Equilibria (NE in short) in polynomial time, even for bimatrix games, understanding the limitations of the approximability of the problem is an important challenge.In this work we study the tractability of a notion of approximate equilibria in bimatrix games, called well supported approximate Nash Equilibria (SuppNE in short). Roughly speaking, while the typical notion of approximate NE demands that each player gets a payoff at least an additive term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…On the other hand, progress on computing approximate-well-supported Nash equilibria has been less forthcoming. The first correct algorithm was provided by Kontogiannis and Spirakis [14] (which shall henceforth be referred to as the KS algorithm), who gave a polynomial time algorithm for finding a 2 3 -WSNE. This was later slightly improved by Fearnley, Goldberg, Savani, and Sørensen [8] (whose algorithm we shall refer to as the FGSS-algorithm), who showed that the WSNEs provided by the KS algorithm could be improved, and this yields a polynomial time algorithm for finding a 0.6608-WSNE; this is the best approximation guarantee for WSNEs that is currently known.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, progress on computing approximate-well-supported Nash equilibria has been less forthcoming. The first correct algorithm was provided by Kontogiannis and Spirakis [14] (which shall henceforth be referred to as the KS algorithm), who gave a polynomial time algorithm for finding a 2 3 -WSNE. This was later slightly improved by Fearnley, Goldberg, Savani, and Sørensen [8] (whose algorithm we shall refer to as the FGSS-algorithm), who showed that the WSNEs provided by the KS algorithm could be improved, and this yields a polynomial time algorithm for finding a 0.6608-WSNE; this is the best approximation guarantee for WSNEs that is currently known.…”
Section: Introductionmentioning
confidence: 99%
“…-WSCE is a refinement of approximate CE that is analogous to well-supported approximate Nash equilibrium, studied in [Kontogiannis and Spirakis 2010;Fearnley et al 2012;Goldberg and Pastink 2014;Babichenko 2013]. In an -Nash equilibrium ( -NE), a player's payoff is allowed to be up to worse than his best response.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, our 0· 732-approximation algorithm substantially improves on the result of [9], both in terms of approximation quality and a more demanding model (communication-bounded algorithms). However, we do not know how to obtain the better approximation quality of [25,12] in the communicationbounded setting. Next we discuss two of the earlier algorithms in the literature whose ideas we use here.…”
Section: Algorithms For Approximate Equilibriamentioning
confidence: 99%
“…The more demanding criterion of well-supported ǫ-Nash equilibrium, disallows a player from allocating positive probability to any pure strategy whose payoff is more than ǫ worse than the best response. Progress on polynomialtime algorithms for this solution concept has been more limited; at this time the lowest ǫ that can be guaranteed by a polynomial-time algorithm is only slightly less than 2 3 [12], obtained via a modification of a 2 3 -approximation algorithm of Kontogiannis and Spirakis [25]. Prior to that, [9] gave a 5 6 -approximation algorithm, that is contingent on a graph-theoretic conjecture.…”
Section: Algorithms For Approximate Equilibriamentioning
confidence: 99%